pengembangan media pembelajaran berbasis augmented reality (AR) pada pembelajaran IPAS topik Panca Indra kelas IV - Asyfa U’qalby; Fahrur Rozi; Nurhairani Nurhairani; Dody Feliks Pandimun Ambarita; Syahrial Syahrial (Jurnal Keluarga Sehat Sejahtera, 2026)
This study aims to determine the validity, practicality, and effectiveness of Augmented Reality (AR)-based learning media in teaching the “Five Senses” topic in the Natural Sciences curriculum for fourth-grade students at SDN 107400 Bandar Khalipah. This study was designed as a research and development (R&D) project using the ADDIE model, which consists of five stages: analyze, design, development, implementation, and evaluation. The data collection techniques used included questionnaires, tests, documentation, and interviews. The subjects of this study were the fourth-grade students at SDN 107400 Bandar Khalipah, totaling 20 students. The research results showed that 82% of the questionnaire validation results fell into the “highly acceptable” category, 84.61% of the material validation test results fell into the “highly acceptable” category, 85% of the test validation results fell into the “highly acceptable” category, 93% of the media validation results fell into the “highly acceptable” category, and the practicality test yielded a score of 90%, falling into the “highly acceptable” category. The effectiveness of the instructional media was determined based on pre-test and post-test scores using the N-Gain percentage formula, yielding a result of 70.13%, which falls into the “moderately effective” category. Based on these data, it can be concluded that this research and development effort has produced a viable, practical, and effective product for use in the learning process.